Good practices of harvest and processing provide high quality Macauba pulp oil. Issue 12 (24th April 2015) - Nunes, Angela A.; Favaro, Simone P.; Galvani, Fabio; Miranda, Cesar H. B.
Abstract : Macauba or macaw palm ( Acrocomia aculeata) has great potential for oil production in tropical American biomes. This work aimed to describe a full set of procedures to obtain high quality crude and refined pulp oil. Crude oil was extracted by forced pressing of dried, mechanically pulped fruits that were collected directly from the bunch at ripening stage. The preliminary refining process sequentially encompassed degumming, neutralization, bleaching, and deodorization. Identity and quality parameters (fatty acid composition, peroxide value, molar absorptivity at 232 and 270 nm, moisture, refractive index, saponification index, unsaponifiable matter, color, total carotenoids, and solid fat content) were determined in all steps. Crude and refined oils presented about 64% of monounsaturated acids (oleic acid) and 26% saturated acids (mostly palmitic acid). Oil composition and physicochemical characteristics were maintained after refining, rendering high quality oil, suitable for multipurpose employments, such as food processing and biodiesel production. Practical applications: Macauba palm is a widespread and high‐yield oil bearing fruit from tropical America that is being domesticated in Brazil. A whole processing of the pulp oil, including fruits from harvest and postharvest, was developed at lab scale to render suitable oil for food and biofuels usages. Going forward, the procedures could be scaled up and the cost effectiveness must be evaluated. The rendered crude and refined oils showed low acidity implying that the synthesis of biodiesel by the traditional and most used alkaline transesterification route is suitable for this raw material. Macauba pulp oil features a high amount of oleic acid, which is a desirable characteristic for the food and biofuel sectors because of the stability against oxidation provided by the monounsaturated fatty acids. The composition of fatty acids, potentially allows the generation of two fractions, olein and stearin, which broads its usages. Good practices of harvesting, processing fruits, and refining, resulted in high oleic quality macauba pulp oil that complies with most standard requirements for crude and refined edible oils. Abstract : Good practices of harvesting, processing fruits, and refining, resulted in high oleic quality macauba pulp oil that complies with most standard requirements for crude and refined edible oils.